2019
DOI: 10.1016/j.ijpharm.2018.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of nanoemulsion and microsuspension formulations of curcuminoids for lung delivery with a novel approach to understanding the aerosol performance of nanoparticles

Abstract: Extensive research has demonstrated the potential effectiveness of curcumin against various diseases, including asthma and cancers. However, few studies have used liquid-based vehicles in the preparation of curcumin formulations. Therefore, the current study proposed the use of nanoemulsion and microsuspension formulations to prepare nebulised curcuminoid for lung delivery. Furthermore, this work expressed a new approach to understanding the aerosol performance of nanoparticles compared to microsuspension form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Genotoxicity using Comet assay showed that the developed NEs are nontoxic at the tested curcuminoid doses suggesting the safety and suitability of the developed NEs. The authors recommend further pre-clinical and clinical studies [ 120 ]. However, additional cytotoxicity evaluation and in vitro release study are also essential in such formulations.…”
Section: Inhalable Anticancer Drug-loaded Lipid-based Nanocarriersmentioning
confidence: 99%
“…Genotoxicity using Comet assay showed that the developed NEs are nontoxic at the tested curcuminoid doses suggesting the safety and suitability of the developed NEs. The authors recommend further pre-clinical and clinical studies [ 120 ]. However, additional cytotoxicity evaluation and in vitro release study are also essential in such formulations.…”
Section: Inhalable Anticancer Drug-loaded Lipid-based Nanocarriersmentioning
confidence: 99%
“…Experimental test system (aim of the study) Test substance/Relevance Exposure conditions Result Comments Relevance of the resultsAyoub et al. () Lymphocytes Nanoemulsion formulations of curcuminoids, prepared using limonene and oleic acid as oil phases.Microsuspension solutions, prepared by suspending curcuminoid particles in isotonic solution (saline solution) of 0.02% Tween 80 (surfactant) Relevance: limited Nanoemulsion tested at three curcumin concentrations (100, 250 and 500 μg/mL)Incubation 30 min at 37 °CComputerised image system to measure Comet parameters, % olive tail moment used for statisticsThe DNA damage observed for six nanoemulsion formulations was lower than that of the negative control indicating some protective effect of the curcumin nanoemulsions Negative Test as reported by Ostling and Johanson, 1984, Singh et al. 1988 and Olive et al., 1990 Low (as in vitro comet)Blasiak et al.…”
Section: Appendix a – Summary Of The Available In Vitro And In Vivo Gmentioning
confidence: 99%
“…Curcuminoids consist of at least three major compounds, including curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC). DMC is one of the main bioactive components of curcuminoids (11), and it is more stable in the blood than other curcuminoids (12). DMC suppressed prostate cancer cell migration and invasion (13) and induced DNA damage and apoptosis in lung cancer cells (14).…”
Section: (Nk) Cells Furthermore Dmc Decreased B and T Cell Proliferation At High Doses Conclusion: Dmc Elevated Macrophage Phagocytosis Imentioning
confidence: 99%